The Study of analysis of student Needs on the Development of integrated Historical Learning model of value of SERAT TJARIOSIPOEN BENAWI SALA to improve Ecological intelligence in SMA Negeri 1 Kalitidu - Dewi, Efha Listiana; Sunardi, Sunardi; Sariyatun, Sariyatun (International Journal of Humanities and Education Development (IJHED), 2020)
This study aims to analyze the needs of students of SMA Negeri 1 Kalitidu for the development of an integrated historical learning model value of SERAT TJARIOSIPOEN BENAWI SALA to improve ecological intelligence. The research method used is the descriptive analysis by analyzing student needs for model development through a questionnaire. The results showed that 96% of students needed and needed the development of an integrated History learning model of SERAT TJARIOSIPOEN BENAWI SALA Value. The integrated history learning of SERAT TJARIOSIPOEN BENAWI SALA Value has strategic meaning in increasing students' ecological intelligence. This learning model can help students to better understand the values contained in the SERAT TJARIOSIPOEN BENAWI SALA Value and improve the ecological intelligence of students.